Meneladani Sikap Abu Bakar As Siddiq Kepada Anak Usia Dini Melalui Metode Cerita Di TK Al-Mustaqiem - Muhammad Basri; Isnaini Kurnia Syahri; Nurul Oktafianti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
One of the characteristics of early childhood is imitation, children can imitate what they see around them. In fostering the attitude of early childhood to become a good person can be trained as early as possible. When instilling a commendable attitude can be done through the story method because the story method aims to train children in communicating, understanding messages or lessons that can be drawn from stories, as well as broadening insight and vocabulary knowledge. This study aims to find out how to use the story method when imitating the attitude of Abu Bakar Ash-Shiddiq in Al-mustaqiem Kindergarten. This study uses qualitative methods that tend to use analysis.